BREAKING THE RULES: PLAYING CRIMINALLY IN VIDEO GAMES - Tregonning, James (Dialogue, 6(2), 2019)
Video games have long courted controversy for their frequent valorisation of criminality. However, in this article, I consider heroic criminals in video games from a different perspective. I focus on two games – Lucas Pope’s Papers, Please (2013) and Osmotic Studio’s Orwell (2016) – that position the player as a low-level government operative in a fictional authoritarian regime. Players are expected to process information for their governments, although they are also given opportunities to undermine or subvert the regime. Thus, the trope of heroic criminal is used to comment on the function and role of the state. It becomes the lens through which issues of political philosophy and ethics are balanced against the more pragmatic concerns of personal safety. These multiple competing pressures allow Papers, Please and Orwell to position heroic criminality as a multifaceted problem for the player to critically engage with. Keywords: Papers, Please; Orwell; video games; criminality; video game violence
Keywords: Type of access: Open Access